Organization of work in Estonian university libraries: a review and survey. Issue 9 (29th August 2014) - Kont, Kate-Riin; Jantson, Signe
Abstract : Purpose: The aim of the current article is to investigate satisfaction of the staff of Estonian university libraries with the organization of work by analyzing characteristics, aspects and dimensions of the work, such as self-realization and skills realization opportunities, task complexity, task interdependence, and fair division of tasks. Design/methodology/approach: The data used in this paper is based on (1) a review of relevant literature to provide an overview of the concept of work organization, and (2) the results of the original online survey created by the paper's authors, conducted among Estonian university libraries. The results are interpreted on the basis of direction in the literature, and the authors' opinions, based on our long-term working experience in Estonian academic libraries. Findings: Although a number of Estonian university librarians were mostly satisfied with the division of labor within their departments, the respondents feel that duties in the library as a whole should be reorganized and workloads should be divided more equally. Almost half of the respondents have performed (in addition to their main job) duties that are not included in their job descriptions.. Originality/value: To the best of the authors' knowledge, no research has been previously carried out in the Estonian library context into work organization and coordination. Based on the current study it can be concluded that the biggest challenge for university libraries in Estonia is to fixate clearly job descriptions and work procedures, divide job duties fairly and guarantee balanced work load. Additional duties should be accompanied with additional remuneration.